Membrane Fouling And Cleaning Study For Drinking Water Treatment Using Integrated Membrane System - Mohamed Nor, Noorlaila (2015)
Membrane technology is being widely applied for water treatment system to enhance the conventional water treatment system. However, there are still some limitations in the application of membrane technology inspite of their advantages due to membrane fouling which resulting to lower production and higher energy consumption. Membrane fouling has been one of the main challenges when the rejected particles accumulated on the membrane surface or inside the pores. Thus membrane cleaning is necessary to minimize fouling effect to the membrane. Current study focus on membrane fouling and cleaning during drinking water production. Research was conducted in Kolej KEDA, Sik, Kedah where a pilot scale integrated membrane system has been installed. The raw surface water from Hutan Lipur Perangin Sik, Kedah was fed directly to the system. The objectives of the research are to evaluate the membrane performance at different operating condition, identify the fouling mechanism of the membrane and propose the appropriate cleaning method. The best performance for the ultrafiltration achieved at TMP 1.0 bar where higher flux produced and lower flux reduction obtained compared to TMP 0.5, 1.5 and 2 bar. Layer cake formation has been found as the dominant fouling mechanism and backwashing at 2 bar for 0.5 minutes was concluded as the most appropriate method which can recover the permeate flux up to 83.69% recovery compared to chemical cleaning using NaClO. By regular backwashing, membrane is expected can be used up to 1339 days.